Effectiveness of concurrent procedures during high tibial osteotomy for medial compartment osteoarthritis: a systematic review and meta-analysis - Lee, O. Sung; Ahn, So Yeon; Ahn, Jin Hwan; Teo, Seow Hui; Lee, Yong Seuk (Springer, 2018)
Introduction: The purpose of this systematic review and meta-analysis was to evaluate the efficacy of concurrent cartilage procedures during high tibial osteotomy (HTO) for medial compartment osteoarthritis (OA) by comparing the outcomes of studies that directly compared the use of HTO plus concurrent cartilage procedures versus HTO alone. Materials and methods: Results that are possible to be compared in more than two articles were presented as forest plots. A 95% confidence interval was calculated for each effect size, and we calculated the I 2 statistic, which presents the percentage of total variation attributable to the heterogeneity among studies. The random effects model was used to calculate the effect size. Results: Seven articles were included to the final analysis. Case groups were composed of HTO without concurrent procedures and control groups were composed of HTO with concurrent procedures such as marrow stimulation procedure, mesenchymal stem cell transplantation, and injection. The case group showed a higher hospital for special surgery score and mean difference was 4.10 [I 2 80.8%, 95% confidence interval (CI) − 9.02 to 4.82]. Mean difference of the mechanical femorotibial angle in five studies was 0.08° (I 2 0%, 95% CI − 0.26 to 0.43). However, improved arthroscopic, histologic, and MRI results were reported in the control group. Conclusion: Our analysis support that concurrent procedures during HTO for medial compartment OA have little beneficial effect regarding clinical and radiological outcomes. However, they might have some beneficial effects in terms of arthroscopic, histologic, and MRI findings even though the quality of healed cartilage is not good as that of original cartilage. Therefore, until now, concurrent procedures for medial compartment OA have been considered optional. Nevertheless, no conclusions can be drawn for younger patients with focal cartilage defects and concomitant varus deformity. This question needs to be addressed separately.